PENGARUH KUALITAS PELAYANAN PUBLIK TERHADAP CITRA BANDAR UDARA INTERNASIONAL SULTAN HASANUDDIN KABUPATEN MAROS - Suryani, Irma; Hakim, Lukman; Razak, Andi Rosdianti (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2025)
The aim of this research is to find out how much influence public service quality variables have on the image of Sultan Hasanuddin International Airport, Maros Regency. The method in this research uses quantitative research methods with descriptive research type. The sampling used the Accidental technique for variable X and variable Y, namely 100 samples. The research results show that the service quality variable analysis is in the very good category with a value of 82.58% and the image variable analysis is in the very good category with a value of 82.02%. Based on the results of linear regression, it shows that the service quality variable has an influence of 0.97 or 97% on image with a significance level of 0.00 which is smaller than 0.05 at Sultan Hasanuddin International Airport, Maros Regency.